Asymmetric Thoracic Metaiodobenzylguanidine (MIBG) Activity Due to Prior Radiation Therapy. (June 2015) - Bai, Xia; Yang, Hua; Zhuang, Hongming
Abstract : Abstract: A 5-year-old patient suffered Horner syndrome, which was caused by a neuroblastoma in the left apex of the lung shown on the initial 123 I-MIBG scan. After the surgical resection and external radiation to the left lung field, a follow-up 123 I-MIBG scan revealed significantly less MIBG activity in the left upper chest compared to the contralateral right upper chest.